Application of the neutron radiography method to study the migration of lithium ions in electric batteries during discharge - Bugybay, Zh.T.; Aitkulov, M.T.; Beisenova, E.E.; Akhanov, A.M. (Recent Contributions to Physics, 2022)
Li-ion batteries are widely used in modern technology as a reliable and stable power source. They are a pair of electrodes separated by a special material impregnated with electrolyte. The charge carriers in such devices are lithium ions. One of the factors affecting the performance of such batteries is the migration of lithium ions. Studies have shown that anisotropic migration of lithium ions on the electrode leads to local lattice dislocations. As a result, the structure of the anode ceases to be heterogeneous, which leads to inefficient movement of charges in it and, accordingly, to a decrease in battery efficiency [1]. Therefore, new types of lithium-ion batteries with increased efficiency are being developed and existing ones are being improved. To this end, research is being carried out, in particular to investigate the migration processes and behavior of lithium in batteries. One of the effective non-destructive methods for such studies is neutron radiography, as the total microscopic cross section of 6Li interaction with neutrons is about 940 barns [2]. In addition, modern neutron radiography facilities allow us to in situ study the internal processes in lithium-ion batteries. This article presents the results of a real-time study of the distribution of lithium in two commercial types of lithium-ion batteries during their discharge. The research was carried out by a non-destructive method at the TITAN neutron radiography facility. As a result of the research, experimental data were obtained on the migration and distribution of lithium in batteries in different states. It is shown that when the battery is discharged, lithium ions migrate to the cathode at a rate of 0.83 ×10-5 and 0.36×10-4 cm/s.